Fatigue sensitivity and mental health among trauma-exposed firefighters. Issue 3 (3rd July 2022) - Kauffman, Brooke; Manning, Kara; Zvolensky, Michael J.; Vujanovic, Anka A.
ABSTRACT: Background: Firefighters are faced with numerous work-related demands and stressors, including exposure to potentially traumatic events, and are thus at an increased risk for poor mental health outcomes. To better understand the mental health of trauma-exposed firefighters, the current study sought to examine the association of fatigue sensitivity with posttraumatic stress disorder (PTSD), anxiety, and depressive symptom severity in a cross-sectional study design. Methods: Participants included 107 ( M age  = 40.8 years; SD age  = 8.95; age range: 21–67 years; 95.0% male) trauma-exposed firefighters. Results: Findings from the current study indicated that fatigue sensitivity was a statistically significant clinical correlate of PTSD, anxiety, and depressive symptom severity. The statistically significant incremental effects were small to medium across the mental health variables, but evident after accounting for years in the fire service, sleep quality, and trauma load. Conclusions: The present data provide initial empirical evidence for the role of fatigue sensitivity in terms of a broad range of mental health indices among trauma-exposed firefighters.